2019
DOI: 10.3389/fpls.2018.01869
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of ß-Ketoacyl Co-A Synthase1 Gene Improves Tolerance of Drought Susceptible Groundnut (Arachis hypogaea L.) Cultivar K-6 by Increased Leaf Epicuticular Wax Accumulation

Abstract: Drought is one of the major environmental constraints affecting the crop productivity worldwide. One of the agricultural challenges today is to develop plants with minimized water utilization and reduced water loss in adverse environmental conditions. Epicuticular waxes play a major role in minimizing water loss. Epicuticular wax covers aerial plant parts and also prevents non-stomatal water loss by forming the outermost barrier from the surfaces. Epicuticular wax content (EWC) variation was found to be affili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 86 publications
6
15
0
Order By: Relevance
“…The de novo synthesis of cuticular wax is initiated from C16 or C18 FAs by various enzymes and transporters, including fatty acyl‐CoA reductase, β‐ketoacyl‐CoA synthase (KCS), and acyl carrier protein (Lewandowska et al., 2020). Consistent with previous studies showing stress‐induced overexpression of KCS1 and ACP4 genes (Lokesh et al., 2019; Wang et al., 2016), two KCS1 genes ( GRMZM2G104626 and GRMZM2G149636 ) were significantly upregulated in the lower leaves under HDP, indicating a functional role in the stress responses. Additionally, two ACP4 genes were differentially expressed in the lower leaves in response to HDP.…”
Section: Discussionsupporting
confidence: 90%
“…The de novo synthesis of cuticular wax is initiated from C16 or C18 FAs by various enzymes and transporters, including fatty acyl‐CoA reductase, β‐ketoacyl‐CoA synthase (KCS), and acyl carrier protein (Lewandowska et al., 2020). Consistent with previous studies showing stress‐induced overexpression of KCS1 and ACP4 genes (Lokesh et al., 2019; Wang et al., 2016), two KCS1 genes ( GRMZM2G104626 and GRMZM2G149636 ) were significantly upregulated in the lower leaves under HDP, indicating a functional role in the stress responses. Additionally, two ACP4 genes were differentially expressed in the lower leaves in response to HDP.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the KCS family members have been functionally characterized in Arabidopsis ( Lee et al, 2009 ; Kim et al, 2013 ; Hegebarth et al, 2017 ), C. sinensis ( Yang H. et al, 2021 ; Wang et al, 2022 ), O . sativa ( Wang X. et al, 2017 ), H. annuus ( González-Mellado et al, 2019 ), S. tuberosum ( Serra et al, 2009 ), M. domestica ( Lian et al, 2021 ), V. vinifera ( Yang Z. et al, 2020 ), and A. hypogaea ( Lokesh et al, 2019 ). However, information about the KCS gene family in passion fruit was unknown and the availability of the passion fruit genome ( Ma et al, 2021 ) made it possible to study on genomic levels.…”
Section: Discussionmentioning
confidence: 99%
“… Yang Z. et al (2020) reported that ectopic overexpression of grape ( Vitis vinifera ) VvKCS in Arabidopsis enhanced the tolerance to salt stress at germination and seedling stages. Overexpression of AhKCS 1 in groundnut ( Arachis hypogaea ) ( Lokesh et al, 2019 ) increased the cuticular waxes and reduced membrane damage under drought stress conditions. Overexpression of BnKCS 1-1/ BnKCS 1-2 in rapeseed ( Brassica napus ) exhibited increased wax concentration and tolerance to drought under drought conditions ( Wang Y. et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several KCS family genes from different plant species were reported to play an important role in regulating cuticle permeability and plant tolerance to abiotic stress. For example, overexpression of AhKCS1 from a drought tolerant groundnut reduced the cuticle permeability and enhanced the drought tolerance in a susceptible genotype by increasing cuticular wax load in leaves ( Lokesh et al, 2019 ). Overexpression of BnKCS1-1 and BnKCS1-2 in Brassica napus also increased drought tolerance in transgenic plants by promoting cuticular wax production ( Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%